2000
DOI: 10.1007/s00585-000-0547-3
|View full text |Cite
|
Sign up to set email alerts
|

Intradiurnal wind variations observed in the lower thermosphere over the South Pole

Abstract: Abstract. The ®rst meteor radar measurements of meridional winds in the lower thermosphere (about 95 5 km), along four azimuth directions: 0°, 90°E, 180°and 90°W; approximately 2°from the geographic South Pole were made during two observational campaigns: January 19, 1995±January 26, 1996, and November 21, 1996±January 27, 1997. Herein we report analyses of the measurement results, obtained during the ®rst campaign, which cover the whole one-year period, with particular emphasis on the transient nature and sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…The PIGW in Fig. 18a are apparently generated like the non-migrating tides through nonlinear coupling between PW and migrating tides, as had been suggested in several papers (e.g., Manson et al, 1982;Manson and Meek, 1990;Forbes et al, 1999;Portnyagin et al, 2000).…”
Section: Planetary-scale Inertio Gravity Wavessupporting
confidence: 59%
See 1 more Smart Citation
“…The PIGW in Fig. 18a are apparently generated like the non-migrating tides through nonlinear coupling between PW and migrating tides, as had been suggested in several papers (e.g., Manson et al, 1982;Manson and Meek, 1990;Forbes et al, 1999;Portnyagin et al, 2000).…”
Section: Planetary-scale Inertio Gravity Wavessupporting
confidence: 59%
“…The inferred large vertical wavelength indicated that a Lamb wave was observed. At the South Pole (88°S ), westward propagating wind oscillations with periods 7 -12 hours were observed with radar measurements (Forbes et al, 1999;Portnyagin et al, 2000). Lamb waves and "normal modes" were invoked, but inertio gravity waves, nonlinear coupling between tides and planetary waves were also suggested as possible explanations.…”
Section: Planetary-scale Inertio Gravity Wavesmentioning
confidence: 95%
“…6 and 7. It is worth remembering here that all periods and time moments of maximum activity are found by wavelet spectra with definite errors (see Portnyagin et al, 2000), and the significance of an oscillation depends on its duration. All of these wind variations have small amplitudes and are presented because they are features of the spectra, which are significant.…”
Section: Long-period (≥4 Days) Oscillationsmentioning
confidence: 99%
“…Hence, we can treat the S-transform spectra of the day-to-day wind variations as if they had been calculated from hourly data. Then we can estimate the peak variance as Portnyagin et al (2000), but should take for an estimation of the primary data variance only independent values of the filtered wind. Thus, we can find significance levels for every frequency in the S-transform spectra.…”
Section: Measurements and Data Analysismentioning
confidence: 99%
“…The S-transform is closely related to the continuous wavelet transform and allows one to determine the absolute phase of an oscillation. The significance level of peaks obtained by using the S-transform may be estimated according to a method presented by Portnyagin et al (2000). To obtain the 4-hourly mean parameters of the semidiurnal tide a sliding harmonic analysis was performed on 48 hour and 72 hour intervals of the hourly-mean wind velocities.…”
Section: Measurements and Data Analysismentioning
confidence: 99%